(untitled) (International Journal of Engineering and Computer Science, 2013)
Key management schemes in sensor networks can be classified broadly into dynamic or static solutions based on whether rekeying (update) of administrative keys is enabled post network deployment.. The objective of key management is to dynamically establish and maintain secure channels among communicating nodes. Many schemes, referred to as static schemes, have adopted the principle of key predistribution with the underlying assumption of a relatively static short-lived network (node replenishments are rare, and keys outlive the network). An emerging class of schemes, dynamic key management schemes, assumes long-lived networks with more frequent addition of new nodes, thus requiring network rekeying for sustained security and survivability. This paper proposes a dynamic key management scheme by combining the advantages of simple cryptography and random key distribution schemes. When the hamming distance between the two nodes is found high, the unique key is changed instead of changing the set of keys and the communication takes place by using any one of the set of key x-oring with the new unique key. The security and performance of the proposed algorithm is compared with the existing dynamic key management scheme based on Exclusion Basis System and prove that the proposed scheme performs better when compared to existing Scheme by considering the number of nodes colluded with time. The result obtained by simulation also shows that the proposed scheme provides security solution and performs better than the existing scheme.